IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP PENINGKATAN JIWA NASIONALISME PESERTA DIDIK DI KABUPATEN SORONG - Dina Suci Yunita; Fardan Abdillah M (Pascasarjana IAIN Sorong, 2022)
This study aims to determine the effect of the implementation of Islamic education learning on increasing the spirit of nationalism of students in Sorong Regency. This study uses quantitative research with a quantitative associative approach. The population of all students who are Muslim in Sorong Regency. Sampling was carried out at SMP Negeri 26 Sorong Regency from class VII-IX. thoroughly by conducting population research with a total of 38 students. Data collection was carried out by distributing questionnaires and analyzing using a simple regression test. The results of this study indicate that the implementation of Islamic Religious Education Learning affects increasing the spirit of nationalism of students in Sorong Regency. This can be seen from the results of a simple regression test with the equation Y = 31,888+.727+e with a constant value of 31,888, and the value of the regression coefficient of Islamic religious education learning is 0.727